A Review: Properties and Applications of Different Grades of Austenitic Stainless Steels and the Effect of Various Factors on the Tensile Behavior Of These Steels (International Journal of Scientific Research and Management (IJSRM), 2015)
Stainless steels (SS) are the most useful category in the family of steels due to their great properties like strength, formability, lustre and corrosion resistance etc. These steels are widely used in many industrial, medical and marine applications etc. In the stainless steels category, the most important steels are austenitic stainless steels (ASSs). The use of stainless steels is growing due to their excellent corrosion resistance, ease of maintenance, attractive appearance, ductility, toughness and fire resistance. These steels can also be strengthened by cold working method to achieve a high ultimate tensile strength (UTS) and yield strength (YS) values. The main objective of the present work is to study about the different grades of austenitic stainless steels and effect of alloying addition on the properties of theses steels.